Aktivitas NADP(H) Oksidoreduktase pada Kultur Sel Kina (Cinchona ledgeriana Moens) Terelisitasi - Maulidiyah Utami; Diah Ratnadewi; Dyah Iswantini; Trivadila Trivadila (Jurnal Ilmu Pertanian Indonesia, 2020)
Cinchona ledgeriana Moens is an industrial plant producing secondary metabolite quinoline alkaloids. To maintain and moreover, to increase the quinoline production especially quinine, in vitro culture system through cell culture could be a potential alternative. If the use of elicitor in cell culture can increase the production of a secondary metabolite, the activity of the enzymes involved in the biosynthetic pathway of the secondary metabolite in question might be increasing. This study aimed to examine the activity of NADPH oxidoreductase in the elicitated cell culture of C. ledgeriana and to evaluate the correlation between the activity of this enzyme and the level of quinine production. The cell cultures of Cinchona were treated with abscisic acid (ABA) or paclobutrazol (PBZ), combined with sucrose, sorbitol, or mannitol in Wood Plant (WP) media, for 7 weeks on a shaker. The quinine concentration was determined using high-performance liquid chromatography (HPLC) and the enzyme activity was measured using fluorometry. The results showed that the highest enzyme activity was found in the P7M cells (PBZ 7 mg/L + mannitol 5.3 g/L + sucrose 20 g/L), followed by the A3S cells (ABA 3 mg/L + sorbitol 5.3 g/L + sucrose 20 g/L). These results correspond to their production level of the quinine alkaloids. The lowest enzyme activity was found in the cultures without elicitor. The increase of NADP(H) enzyme activity in the P7M and A3S treatments were 13.5 and 8.5%, respectively, compared to that in the control cells. Keywords: elicitation, fluorometry, NADP(H) oxidoreductase, quinoline alkaloid